NUP98-NSD1 Driven MDS/MPN in Childhood Masquerading as JMML. Issue 6 (August 2021) - Behnert, Astrid; Lee, Alex G.; Young, Elizabeth P.; Breese, Marcus R.; Leung, Stanley G.; Behroozfard, Inge; Maruffi, Maria; Sweet-Cordero, E. Alejandro; Dvorak, Christopher C.; Chu, Julia; Stieglitz, Elliot
Abstract : Overlapping myelodysplastic/myeloproliferative neoplasms (MDS/MPN) are clonal hematopoietic disorders with features of myelodysplasia and myeloproliferation. The only well-characterized MDS/MPN in children is juvenile myelomonocytic leukemia, an aggressive disorder of infants and toddlers. The biochemical hallmark of this disease is hyperactivation of the Ras/MAPK signaling pathway caused by mutations in Ras pathway genes in more than 90% of patients. Translocations involving receptor tyrosine kinases have been identified in rare cases. Here, we report a 2-year-old patient who presented with MDS/MPN driven by a cytogenetically cryptic NUP98-NSD1 fusion, a translocation thought to exclusively occur in patients with acute myeloid leukemia. Abstract : Supplemental Digital Content is available in the text.